2005
DOI: 10.1038/sj.cr.7290267
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide: orchestrating hypoxia regulation through mitochondrial respiration and the endoplasmic reticulum stress response

Abstract: Mitochondria have long been considered to be the powerhouse of the living cell, generating energy in the form of the molecule ATP via the process of oxidative phosphorylation. In the past 20 years, it has been recognised that they also play an important role in the implementation of apoptosis, or programmed cell death. More recently it has become evident that mitochondria also participate in the orchestration of cellular defence responses. At physiological concentrations, the gaseous molecule nitric oxide (NO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
51
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 16 publications
0
51
0
1
Order By: Relevance
“…Hypoxia is known to upregulate transcription factor HIF1 activating expression of genes involved in angiogenesis [43]. However, it was demonstrated that co-existence of both hypoxia and lower NO concentration caused a rapid decrease in HIF1 [44,45] that may represent one of the mechanisms involved in anti-angiogenic efect of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is known to upregulate transcription factor HIF1 activating expression of genes involved in angiogenesis [43]. However, it was demonstrated that co-existence of both hypoxia and lower NO concentration caused a rapid decrease in HIF1 [44,45] that may represent one of the mechanisms involved in anti-angiogenic efect of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been documented that NO exerts several actions on cell respiration, particularly that NO is able to inhibit complex IV in the respiratory chain on mitochondria (Brunori et al, 2004). As a result of this inhibition, NO has been reported to posses both pro-apoptotic and anti-apoptotic effects (Beltran et al, 2000;Xu et al, 2005). Because apoptosis appears to be the main mechanism leading to oligodendrocyte death in this model (Arnett et al, 2002), it is possible that differences in time, dose, and site of NO secretion by the different NOS isoforms in response to cuprizone may lead to divergent effects in oligodendrocyte apoptosis and, therefore, explain the differences between the various NOS mutant strains and wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…The very high levels of NO shown in the present study are capable of inhibiting oxygen consumption by the mitochondria sufficient to decrease ATP synthesis. This can create a condition we have called 'nitroxia', which is associated with high levels of NO, oxygen and impaired mitochondrial bioenergetics [5,6]. The highly reducing status of the mitochondrial respiratory chain in the presence of oxygen will then promote superoxide formation.…”
mentioning
confidence: 99%
“…However, the story became more complex with the recognition that NO serves as a ligand for other haem proteins such as COX (cytochrome c oxidase) in the mitochondria and haemoglobin in the red blood cell [2,3]. The fact that NO interacts with the haem groups that normally bind oxygen essentially expanded the role of NO in cell signalling from a simple haem ligand to a regulatory modulator of oxygen-sensitive processes [4][5][6].…”
mentioning
confidence: 99%
See 1 more Smart Citation